Analisis Nilai Moral Tokoh-Tokoh Dalam Serial Animasi "Riko The Series" Pada Episode 15 Season 2 “Adab Sebelum Ilmu” - Ahmad Hariandi; Pooja Rekha Larasati; Eka Karlina; Arumningtias Dewi Saputri; Zilvad Larozza (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
Nowadays's increasingly sophisticated technological development can influence a person's character or personality. Implanting a moral fiber in children should be done along with the advent of technology. Youtube as a social media platform that provides videos to watch can become a device for children's moral imposition with the technology media, among other things the rico series's animation. The study was on analysis of the moral role in the animation series 2episode 15 adab before science. The purpose of this study is to learn the moral values of the animation of rico the series in episode 15 of season 2 with the title adab before science. The study USES qualitative research methods using library study data collection techniques, note and document. The analysis technique used was with Roland barthes' semiotics technique concerning petanda relationships and markers in a mark of meaning. This analysis was done by watching the animation of rico the series on episode 15 of the 2nd season, before science, before science, create a synopsis, and express the meaning of the words and conduct of the characters and the values it contains. The results of this study have been found in the animated series in the 15th episode of culture before the study of the moral value to god consists of saying hello, thanking, and admiring god's greatness, the moral value to the family of counseling in goodness, please help and forgive, and the moral value to oneself of apologizing and acknowledging it.